A inclusão da abundância na diversidade funcional aumenta o seu poder de previsão?: teste em uma comunidade de cerrado - Miatto, Raquel Carolina (2011)
Assuming that traditional measures of diversity are rough predictors of functioning and that measures that incoporate information about functional traits are better predictors than the traditional ones, functional diversity measures are intensely used nowadays. However, whether the inclusion of functional traits in biodiversity estimation indeed increases our predictive power is rarely tested. Moreover, dendrogram-based functional diversity measures usually do not take abundance into account. By sampling a southern cerrado site in Brazil, we tested whether, when compared to traditional diversity measures, the inclusion of functional traits leads to an increased predictive power in relating functional diversity to community functioning. We demonstrated that it is possible to include abundance in dendrogram-based functional diversity, and tested whether, when compared to functional diversity as usually calculated, the inclusion of abundance leads to an increased predictive power. No diversity measure was related to community functioning, including functional diversity. Nevertheless, we showed that it is possible to include abundance in dendrogram16 based functional diversity measures, even if most indices were correlated with each other.